2008
DOI: 10.1161/hypertensionaha.107.096016
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Augmentation Index Defines the Relationship Between Central and Peripheral Pulse Pressure

Abstract: Abstract-Peripheral systolic blood pressure is amplified above central aortic systolic pressure, but the late systolic shoulder of the peripheral pulse may approximate central systolic pressure. Because late systolic pressure also determines the peripheral augmentation index, a measure of pressure wave reflection within the systemic circulation, this implies a direct relationship between amplification and augmentation. We compared the late systolic shoulder of the peripheral pressure waveform with estimates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 31 publications
(29 reference statements)
11
116
2
Order By: Relevance
“…These authors also found a positive correlation (r¼0.82, Po0.001) between CAIx estimated with SphygmoCor and rAIx estimated with HEM-9010AI, similar to that seen in our study with SphygmoCor (r¼0.86, Po0.01) but greater than that found between CAIx estimated with SphygmoCor, and rAIx estimated with B-Pro (r¼0.46, Po0.01). The rAIx values reported by both Kohara et al 14 (0.69±16.3 in males and 0.81±16.1 in females) and Munir et al 13 (0.79 ± 11.8) are lower than those obtained in our study. However, considering that the correlation of our data using SphygmoCor coincides with the results of other authors 13,14 and is in disagreement with the estimation of rAIx using B-Pro, it would seem necessary to revise the methodology used by this device in estimating this parameter.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…These authors also found a positive correlation (r¼0.82, Po0.001) between CAIx estimated with SphygmoCor and rAIx estimated with HEM-9010AI, similar to that seen in our study with SphygmoCor (r¼0.86, Po0.01) but greater than that found between CAIx estimated with SphygmoCor, and rAIx estimated with B-Pro (r¼0.46, Po0.01). The rAIx values reported by both Kohara et al 14 (0.69±16.3 in males and 0.81±16.1 in females) and Munir et al 13 (0.79 ± 11.8) are lower than those obtained in our study. However, considering that the correlation of our data using SphygmoCor coincides with the results of other authors 13,14 and is in disagreement with the estimation of rAIx using B-Pro, it would seem necessary to revise the methodology used by this device in estimating this parameter.…”
Section: Discussioncontrasting
confidence: 82%
“…12 The increases in central blood pressure, mean blood pressure and rAIx were estimated as well. rAIx was calculated from the radial wave pulse as follows: (second peak SBP (SBP2)ÀDBP)/(first peak SBPÀDBP)Â100, 13 as seen in Figure 1. Intra-observer reliability evaluated in 20 subjects before the study began, using the intraclass correlation coefficient, showed values of 0.971 (95%CI: 0.923-0.989) for CASP and 0.952 (95%CI: 0.871-0.982) for rAIx.…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…As the changes in P2 and AIx were correlated and Tr was unaffected after PV, our data suggest that the post-vibration AIx response could be mainly driven by a reduction in vascular smooth muscle tone in the legs. 30,31 The aortic pressure pulse wave is a composite of an early forward wave (P1) and a reflected wave traveling from the periphery back to the aorta (P2). 6 In cardiac patients with increased AIx, aortic SBP is determined by P2 whereas peripheral SBP is more dependent on P1.…”
Section: Discussionmentioning
confidence: 99%